Modern Designs Using Parabolic Curves as a New Paradigm for Sophisticated Architecture - Mishra, Rozy; Sahani, Suresh Kumar (Asian Journal of Science, Technology, Engineering, and Art, 2024)
This research investigates the spatial aspects of architecture through the practical use of parabolic curves, suggesting that these curves are an architectural advancement in the direction of the creation of complex, efficient and beautiful buildings. Focused on material properties and environmental concerns, as well as the strength of the structure, the study explores the use of parabolic geometry in modern architecture. The integration of case studies, computational modeling, and theoretical analysis is done in an interdisciplinary context. The study comprises: 1) Theoretical Framework: A survey of the geometrical and historical importance of parabolas in architectural design; 2) Computational Modeling: The processes of design tools for parabolic structures and evaluation of their load, material, and aesthetic efficiency; 3) Case Studies: Studies of modern buildings that include parabolic curves in their designs, including well-known buildings and new tendencies in Eco-Architecture.